2017
DOI: 10.1111/jpn.12827
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary supplementation with Aurantiochytrium limacinum on lactating dairy cows in terms of animal health, productivity and milk composition

Abstract: The aim of this study was to investigate the effect of dietary supplementation with the docosahexaenoic acid (DHA)-rich microalgae, Aurantiochytrium limacinum (AURA), on a variety of health and productivity parameters in lactating cows. Twenty-four cows were blocked by parity and number of days in milk and then randomly assigned to a control (CON; n = 12) group with no algal supplementation, or a treatment group (AURA; n = 12) provided with 100 g AURA cow day or 16 g DHA cow day . A variety of health and produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
32
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 56 publications
7
32
0
1
Order By: Relevance
“…Previously, Moran et al (2017a) found that DHA concentration and conservation efficiency from algae to milk dramatically raised up to 20% during 21 days, then reached the plateau (between 21-22%) 7 days later. In contrast, Moran et al (2017b) found higher average efficiencies ratio (7 and 18%) in dairy cows fed Aurantiochytrium limacinum enriched fodder (105 or 146 g/day/cow) during the 12-week treatment. Other study reported that transfer efficiency was 8.9 in cows fed 125-375 g/day marine algae (Moate et al, 2013).…”
Section: Discussionmentioning
confidence: 59%
“…Previously, Moran et al (2017a) found that DHA concentration and conservation efficiency from algae to milk dramatically raised up to 20% during 21 days, then reached the plateau (between 21-22%) 7 days later. In contrast, Moran et al (2017b) found higher average efficiencies ratio (7 and 18%) in dairy cows fed Aurantiochytrium limacinum enriched fodder (105 or 146 g/day/cow) during the 12-week treatment. Other study reported that transfer efficiency was 8.9 in cows fed 125-375 g/day marine algae (Moate et al, 2013).…”
Section: Discussionmentioning
confidence: 59%
“…Nevertheless, the effects of supplementing microalgae biomass to ruminants on the biohydrogenation of C18 FA, as well as its effects on milk fat depression have been little studied. In fact, the only study available seems to be with lactating dairy cows fed Aurantiochytrium limacinum biomass, a DHA-rich microalga, where no effects on milk fat depression, as well as on health and productivity parameters, were found 49 . As far as we know there are no studies of the inclusion of P. tricornutum or N. oceanica biomass in dairy ruminants.…”
Section: Discussionmentioning
confidence: 99%
“…has been shown to increase the DHA content of broiler meat [ 13 ], while maintaining consumer acceptability without reducing shelf life [ 14 ]. Aurantiochytrium limacinum, a related microalgae, when grown heterotrophically on a low-sodium medium has also been shown to increase the DHA content of cows’ milk [ 15 , 16 ], of pig muscle tissue [ 17 , 18 ], and hens’ eggs [ 19 ].…”
Section: Introductionmentioning
confidence: 99%